TRANSITIVITY ANALYSIS OF PRESIDENTIAL DEBATE BETWEEN TRUMP AND BIDEN IN 2020 - Rani Fadilah; Heri Kuswoyo (Linguistics and Literature Students' Journal, 2021)
This study was aimed at investigating the transitivity properties (processes, participants, and circumstances) used in the presidential debate between Donald Trump and Joe Biden in presidential election debate in 2020. The aim of this study was also to investigate the types of transitivity processes and the most dominant process occured in the debate. Using a library study, the data were obtained from two transcription of debate. The data were analyzed qualitatively using Halliday’s (1994) and Halliday and Halliday Matthiessen (2014) theories.The findings showed that all types of processes, including material, mental, verbal, relational, existential, and behavioral processes, were found. The material process was significantly applied both two debaters. This indicates that the debaters had progressed to the stage of the material process. In other words, they all focused on the speaker's objectives, they were aware of the realization aspect of society action. To conclude, it was about the intentions, purposes, and directions of the arguments in the presidential debate between Trump and Biden about the critical crisis that the US was facing.Keywords: Systemic functional linguistics, transitivity processes, presidential debate between Trump and Biden.